Sacrificio e sacerdozio a Qumran - Martone, Corrado (Studi e materiali di storia delle religioni, 2021)
This essay deals with the question of the presence of sacrifice in Qumran. It analyzes various texts that, despite the detachment of the group from the temple in Jerusalem, seem to testify to some form of survival of the sacrificial practice. Particular attention is paid to the possibility of a transposition of the sacrificial liturgy on an eschatological level. An appendix is dedicated to this question from an archaeological point of view. (English)